PENGARUH HIPNOTERAPI TERHADAP PENURUNAN KECEMASAN IBU HAMIL DAN BERSALIN - Shandy Wigya Mahanani; Umaroh Umaroh; Isnu Kurnia Nugrahaeni; Aida Amalia Nur Ramadhian (Midwifery Care Journal, 2022)
Psychological problems underlying the fear and anxiety will be embedded in the mother's subconscious mind, becoming negative thoughts. The psychological burden can lead to problems with labor complications, which interfere with the normal process of pregnancy and childbirth. The psychological condition of the mother who is less supportive can cause stress which can cause tense muscles, stiffness, labor pain and hard, inelastic birth canal. Negative thoughts accompanied by pain, will improve the work of the sympathetic nervous system. The hypothalamus sends a signal to the pituitary gland, to reduce the hormone cortisol, which is a stress hormone, so that the autonomic nervous system activates the adrenal glands causing physical tension in pregnant women which causes more pain. The purpose of this study was to determine the effect of hypnotherayi on reducing anxiety of pregnant and maternal mothers. This research article reviewed from electronic databases including Science Direct, Google Scholar and other related websites. The number of keywords used included 7 "Hypnotherapy" and "anxiety" From 1484 Publications ranging from 2008 to 2018, the use of the hypnotherapy method to reduce anxiety in pregnant women was presented in English, included in this review. Pregnant women who take hypnotherapy can reduce anxiety, gain peace of mind and instill positive thoughts on the subconscious mind because during the hypnotherapy process the mother experiences deep physical relaxation, focused attention, increased sensory ability, and relaxed control.